Simulation of Fundamentals of Space Curves using JavaScript - Dhakal, Bed Prasad (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
This qualitative case study explores pre-serve teachers understanding on fundamentals of space curve in three-dimensional differential geometry, while studying at master level at Tribhuvan University in Nepal. The Technological-Pedagogical-Content-Knowledge (TPCAK) theoretical model was used to explore their understanding particularly on three fundamental vectors: tangent, principal normal and binormal vectors and three fundamental planes: osculating plane, normal plane and rectifying plane. In this study, there were thirteen participants, who were studying the course “Differential Geometry” using teacher made JavaScript based 3D visualizations. After the analysis of participants understanding on learning content, it is found that they gain enhanced conceptual understanding through interactive-concept-image of the concept definition.